The Role of Microbial Mats in the Removal of Hexavalent Chromium and Associated Shifts in Their Bacterial Community Composition - Abed, Raeid M. M.; Shanti, Mary; Muthukrishnan, Thirumahal; Al-Riyami, Zayana; Pracejus, Bernhard; Moraetis, Daniel (Frontiers in Microbiology, 2020)
Microbial mats are rarely reported for chromium-polluted ecosystems, hence information on their bacterial diversity and role in chromium removal are very scarce. We investigated the role of nine microbial mats, collected from three quarry sumps of chromium mining sites, in the removal of hexavalent chromium (Cr(VI)). Bacterial diversity in these mats and community shifts after incubation with Cr(VI) have been investigated using MiSeq sequencing. In nature, a chromium content of 1,911±100 mg kg-1 was measured in the microbial mats, constituting the third highest source of environmentally available chromium. The mats were able to remove 1 mg l-1 of Cr(VI) in 7 days under aerobic and anaerobic conditions. MiSeq sequencing of the original mats yielded 46-99% of the sequences affiliated to Proteobacteria, Firmicutes and Actinobacteria. When the mats were incubated with Cr(VI), the bacterial community shifted in the favor of Alphaproteobacteria and Verrucomicrobiae. We conclude that microbial mats in the quarry sumps harbor diverse microorganisms with the ability to remove toxic Cr(VI), hence these mats can be potentially used to remove chromium from polluted waters.